1972
DOI: 10.1073/pnas.69.11.3247
|View full text |Cite
|
Sign up to set email alerts
|

A Particle Associated with the Polyadenylate Segment in Mammalian Messenger RNA

Abstract: A structure consisting of poly(A) complexed with other components is released from polysomes by ribonuclease treatment. The poly(A) complex has a sedimentation value of 12-15, while the corresponding sedimentation value for free poly(A) is 4. The complex does not appear to represent an artifact formed by interaction of free poly(A) with either cytoplasmic or polysomal proteins. The polynucleotide released from the complex by treatment with sodium dodecyl sulfate shows the same electrophoretic mobility as that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(40 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…The same RNP could be identified by sedimentation in a sucrose gradient, and a similar complex of lower sedimentation value was obtained by incubating synthetic [sH]poly(A) with crude cytoplasmic protein. These results suggested a role for the 3'-poly(A) segment of mRNA as a specific protein binding site (34), and other investigators have reported poly(A)-protein complexes with various partially purified cell fractions (35,36).…”
Section: Methodsmentioning
confidence: 62%
See 1 more Smart Citation
“…The same RNP could be identified by sedimentation in a sucrose gradient, and a similar complex of lower sedimentation value was obtained by incubating synthetic [sH]poly(A) with crude cytoplasmic protein. These results suggested a role for the 3'-poly(A) segment of mRNA as a specific protein binding site (34), and other investigators have reported poly(A)-protein complexes with various partially purified cell fractions (35,36).…”
Section: Methodsmentioning
confidence: 62%
“…Recently, Kwan and Brawerman (34) reported a complex between protein and the 3'-poly(A) segment of mouse sarcoma 180 mRNA. This complex was identified by retention of labeled RNP on a nitrocellulose filter under conditions in which deproteinized or free polyribonucleotide passed through the filter (34). The same RNP could be identified by sedimentation in a sucrose gradient, and a similar complex of lower sedimentation value was obtained by incubating synthetic [sH]poly(A) with crude cytoplasmic protein.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is now known that specific proteins are found associated with the poly(A) regions of globin mRNA [42,43] and these may be required for translation or re-initiation to proceed. If this is the case, degradation of the poly(A) sequence past a certain defined point (say approximately 40 nucleotides in length) might remove this protein and prevent successful re-initiation.…”
Section: Elution From Poly( U)-sepharose With Pormamide Gradientsmentioning
confidence: 99%
“…The role of PABP in mRNA metabolism is also unclear, although its highly specific binding properties imply that its function is linked with at least one function of poly(A) (9,35). The molecular weight of cytoplasmic PABP varies from 72,000 in mammals (9,23) to 68,000 in Saccharomyces cerevisiae (2,58,59) to 31,000 in slime molds (36,37).…”
mentioning
confidence: 99%